The secret life leaves - Jensen, Lawrence; Chung, Andrew (New Zealand : ETI ; Dr. Lawrence Jensen, 2004)
Three dimensional animations, supported by authoritative narrations, explore the leaf surface and explain the functioning of the guard cells. The viewer is then taken inside the leaf to see the photosynthetic and conducting cells
Title from title screen
Editors, animation , Andrew Chung
Narrator: Richard Smith
Keywords: Leaves -- Anatomy; Leaves